2017
DOI: 10.1515/med-2017-0064
|View full text |Cite
|
Sign up to set email alerts
|

HIV/STI prevention interventions: A systematic review and meta-analysis

Abstract: AbstractBehavioral interventions can prevent the transmission of HIV and sexually transmitted infections. This systematic review and meta-analysis assesses the effectiveness and quality of available evidence of HIV prevention interventions for people living with HIV in high-income settings. Searches were conducted in MEDLINE, EMBASE, PsycINFO, and CDC Compendium of Effective Interventions. Interventions published between January, 1998 and September, 2015 were included. Quality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 65 publications
0
11
0
Order By: Relevance
“…This is the first time to evaluate the efficacy of HIV intervention in Chinese migrants. Several reviews (Crepaz et al., 2006 ; Crepaz et al., 2014 ; Globerman et al., 2017 ) studied the efficacy of HIV preventive interventions for people living with HIV in high-income settings, these studies focused on the specific methods of intervention among HIV patients, suggested that comprehensive risk counseling and services, provided skills building were effective in reducing sexual risk behaviors. While our study focused on the overall efficacy of HIV/AIDS interventions and the influencing factors of efficacy among migrants in China, our study suggested that the intervention conducted among migrants in China was effective in altering their knowledge, attitude, and behaviors on HIV/AIDS.…”
Section: Discussionmentioning
confidence: 99%
“…This is the first time to evaluate the efficacy of HIV intervention in Chinese migrants. Several reviews (Crepaz et al., 2006 ; Crepaz et al., 2014 ; Globerman et al., 2017 ) studied the efficacy of HIV preventive interventions for people living with HIV in high-income settings, these studies focused on the specific methods of intervention among HIV patients, suggested that comprehensive risk counseling and services, provided skills building were effective in reducing sexual risk behaviors. While our study focused on the overall efficacy of HIV/AIDS interventions and the influencing factors of efficacy among migrants in China, our study suggested that the intervention conducted among migrants in China was effective in altering their knowledge, attitude, and behaviors on HIV/AIDS.…”
Section: Discussionmentioning
confidence: 99%
“…More broadly, a number of interventions have been developed that focus on promoting sexual and reproductive health and rights among those living with HIV, with the goal of preventing transmission and repeated exposure to the virus among individuals living with HIV. A significant number of studies have been conducted in the USA,7 8 and findings from low/middle-income countries have demonstrated mixed results 9–11. For example, in a prevention intervention among people living with HIV receiving treatment in clinical settings in Thailand a reduction in unprotected sex was observed overall, but not among men who have sex with men.…”
Section: Introductionmentioning
confidence: 99%
“…In June 2016, the United Nations General Assembly High-Level Meeting on AIDS (Acquired Immune Deficiency Syndrome) adopted the United Nations Political Declaration on HIV (Human Immunodeficiency Virus) that aims to end the AIDS epidemic by 2030 (UNAIDS, 2016). However, the number of people living with HIV remains high (Globerman et al, 2017). In 2016, worldwide 36.7 million people were living with HIV (as compared to 35 million in 2013 and 33.3 million in 2010) and 1.8 million (as compared to 2.1 million in 2013 and 2.6 million in 2010) were newly infected (UNAIDS, 2011(UNAIDS, , 2014(UNAIDS, , 2017.…”
Section: General Introductionmentioning
confidence: 99%
“…Even after more than 20 years of evidence-based behavioral interventions to reduce sexually transmitted infections (STIs), including infections with the human immunodeficiency virus (HIV), the number of people living with STIs and/or HIV remains high (Globerman et al, 2017). In particular, young people aged 15-24 years are at high risk of acquiring STIs (Centers for Disease Control and Prevention, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation